Perencaan Strategik Melalui Analisis SWOT Di Tkit At-Taqwa Grabag Magelang - Nidaul Munafiah (Raudhatul Athfal: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
Observations and assessments carried out simultaneously on the external and internal environment of educational institutions enable education managers to be able to identify various types of opportunities to formulate and implement education plans. A comprehensive design can be carried out through an action process known as strategic planning or management. Strategic planning of an institution can be done using the SWOT analysis method (Strength, Weakneses, Opportunities and Threats) through qualitative and quantitative approaches. The TKIT At-Taqwa Institute which is located at Ponggol 2 Grabag Magelang Regency is one of the educational institutions that has many opportunities and strengths and can not be separated from weaknesses and challenges in the need to carry out strategic planning to develop themselves towards a better direction. Specifically, this paper aims to identify and analyze the strengths, weaknesses, opportunities and threats that exist at TKIT At-Taqwa Grabag to map and make the next step in strategic planning. Based on the SWOT analysis that has been done, the At-Taqwa Grabag TKIT education institution is in the quadrant I position with the results of the strength-weakness analysis: 73.5- 64.0 = 9.5 and opportunities - threats: 63.5– 62.5 = 1